Superelasticity in Polycrystalline Ni-Mn-Ga-Fe Microwires Fabricated by Melt-extraction - Liu,Yanfen (2015)
Ni48Mn26.4Ga19.7Fe5.9 microwires with grain size of 1-3 micron were successfully fabricated by melt-extraction. The superelastic effects in the microwires under various temperatures and loads were systematically demonstrated. The as-extracted microwires displayed partial superelasticity when attended at relatively high temperature. The critical stress for stress-induced martensite formation increases linearly with temperature and follows the Clausius-Clapeyron relationship. The temperature dependence of the as-extracted polycrystalline Ni48Mn26.4Ga19.7Fe5.9 microwires is 16.4 MPa/K, which is higher compared with Ni-Mn-Ga single crystals. In addition, the as-extracted microwires display excellent shape memory behavior with the recovery strain and recovery ratio of 1.26% and 86%, respectively, when the total strain reaches 1.47% at 310 K.